The application of photogrammetric orthomosaic for field documentation of palaeontological sites - Díaz Martínez, Ignacio (2018)
Field work is crucial in palaeontological studies. Whether in case the fossils are extracted from the site, or they are studied in situ, an exhaustive documentation of the fossil remains and their reciprocal position within the rocks are necessary for any future study, including taphonomical, palaeoecological and systematical analyses. For this purpose, the digital photogrammetry is a powerful and non-invasive methodology that can help palaeontologists in their fieldtrip works. This discipline allows to create an orthomosaic and reconstruct an object in 3D through 2D photographs capturing the scene from multiple angles and with sufficient overlap. An orthomosaic is an image composed of a collection of photos in which the geometric distortion has been corrected and orthorectified such that the scale is uniform. Both in sites which are studied in situ as in which the fossils are extracted, the orthomosaic allow to document faster and more accurate than with conventional methods producing a precise orthogonal X-Y scheme of the site. Moreover, during excavations, it is advisable to generate an orthomosaic before and after the extraction of each fossil, and analyze all the overlapping information subsequently. Indeed, by adding the vertical (Z) information of the 3D model, tridimensional position (X,Y,Z) of all the specimens can be reconstructed in each stage of the excavation, and very precise 3D taphonomic maps can be obtained. Generation of orthomosaic turned out to be a effective tool for checking and correcting the relative and absolute position and the parameters related to palaeontological field data.